Risk of fall (RoF) intervention by affecting visual egocenter through gait analysis and yoked prisms. - Padula, William V.; Subramanian, Prem; Spurling, April; Jenness, Jonathan (NeuroRehabilitation, 2015)
BACKGROUND: Following a neurologic event such as traumatic brain injury (TBI), cerebrovascular accident (CVA), and chronic neurological conditions including Parkinson's disease, multiple sclerosis, and cerebral palsy a shift in the visual midline (egocenter) can directly affect posture, balance and spatial orientation. As a consequence, this increases the risk of fall (RoF) and injury that imposes a major financial burden on the public health system. OBJECTIVE: To determine if there is a statistically significant change in balance with the intervention of yoked prisms to reduce the risk of fall in subjects with neurological impairments. METHODS: Ambulation of thirty-six subjects was evaluated on a pressure sensitive mat before and after intervention with yoked prisms. Changes in gait and balance were analyzed in the anterior-posterior (AP) and medial-lateral (ML) axes during ambulation. RESULTS: T-tests for each measure comparing the difference-of-differences to a zero change at baseline returned statistically significant reductions in both AP (p < 0.0001; 95% CI: 1.368-2.976) and ML (p = 0.0002; 95% CI: 1.472-1.173) imbalances using specifically directed yoked prisms to correct the visual midline deviation. CONCLUSION: These findings demonstrate that yoked prisms have the potential to provide a cost-effective means to restore the visual midline thereby improving balance, reduce RoF and subsequent injury.